Current concepts related to the diagnosis and treatment of hemangioma: literature review (Research, Society and Development, 2021)
Hemangioma is a tumor considered histologically benign of mesenchymal origin, characterized by the formation of vascular endothelial cells and can be divided into two types, capillary and cavernous, depending on the dominant microscopic size of the vessels. Therefore, the aim of the present study was to analyze what exists in the specialized literature on the diagnosis and treatment of hemangioma. This study was carried out based on bibliographic research, in the respective databases: Pubmed and CAPES Periodicals between the years 2011 and 2020. The research was carried out at DeCS (Health Sciences Descriptors) to choose the descriptors: “Oral Pathology”; “Diagnosis” and “Vascular Malformations”. Ten scientific productions that met the inclusion criteria and were selected. The diagnosis of hemangioma, except in intraosseous cases, can be easily established in a simple and safe way through anamnesis, clinical examination and through semi-technical maneuvers, such as vitro pressure, in most cases this maneuver is conclusive. Because it is a vascular lesion, incisional biopsy is contraindicated in these cases, due to the great risk of bleeding.